Equi the Philippine Institute of Horticultural Research - Reyes, Andrew John P.; Perion, Sharon S. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
Horticulture is the small scale perspective on plant cultivation. With it, the possibility of creating small developmental modules on agricultural fields becomes easy and contextual, becoming an integral instrument in aiding the solving of the agriculture decline within the country. Tapping into the potential of horticulture, there is a need to see this branch of agriculture in a multi-faceted view. Focusing on research creates a scientific skeleton that allows the system to expand its procedural and informative well. Focusing on recreation creates an approachable collaborative scheme that allows the system to be the bridge between the laymen and the professionals. Focusing on gardening creates a natural setting for cultivation that allows the system to provide applicable modules for the community. Focusing on academics creates a future industry foundation through scholastic endeavors that allows the system to persist through the coming generations. Research, recreation, gardening, and academics is an integral system of procedural and programmatic relationships that shall allow Equi to work as an institute of horticultural research.
include appendices
Best Thesis (Architecture) AY 2018-2019, 3rd place
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Horticulture; Horticulture -- Philippines